Smart Door Lock Dengan Face Recognition Untuk Keamanan Akses Ruang Server - Mardiani, Eri; Supriyanti, Dedeh; Septya, Sharmila; Purnata, Alan (UNIVERSITAS RAHARJA, 2024)
PT. Fiber Networks Indonesia is an Internet Service Provider (ISP) that has installed a Base Transceiver Station (BTS) in the Jabodetabek area. Access to the BTS server room is currently via manual access using a regular key. All ISPs want to immediately resolve existing problems so that their customers remain connected and stable. Access to the server room door is still compromised from a security perspective and can still be accessed easily by irresponsible individuals. The aim of this research is to develop a Smart Door Lock prototype with Face Recognition for security access to the server room. This prototype tool uses Raspberry Pi-based facial recognition for entry access and a camera for facial detection and recognition. Flask framework web-based application that simplifies the Internet as a medium for communication, access and data storage. As well as using a Solenoid Door Lock as an actuator. The test results show that it is able to recognize registered faces and open the door. If there is an unfamiliar face, the solednoid will remain locked and the door will not open. Infiltration user data and infiltration attempts (intruders) are stored as logs or history in the SQLite 3 database and Raspberry Pi internal storage, making it easy to review the data if needed at a later date.